Methods for simplifying mathematical models of dynamical systems - Gorodetskyi, Viktor; Osadchuk, Mykola (Моделювання, керування та інформаційні технології, 2023)
We consider the problem of simplifying a system of ordinary differential equations obtained as a result of reconstruction from a single observed variable. To solve the problem, we propose two methods: analytical and numerical-analytical. Both methods were applied to a third-order system of ordinary differential equations with polynomial right-hand sides and the results of the methods were compared. Розглянута задача спрощення системи звичайних диференціальних рівнянь, отриманої як результат реконструкції за однєю спостережуваною змінною. Для розв’язання задачі запропоновано два методи – аналітичний та чисельно-аналітичний. Обидва методи були застосовані до системи звичайних диференціальних рівнянь третього порядку з поліноміальними правими частинами і було виконано порівняння результатів методів.